Simulacra Politics: Digital Advertising for the 2024 Presidential Election on Social Media - Yudi Daherman; Happy Wulandari (Borong Newinera Publisher, 2024)
The presidential election in Indonesia will be held in 2024, but the excitement of conversations on various social media platforms has been felt at this time. This political party, which is held every 5 years, has attracted a lot of public attention, one of which is through political advertising on social media. Social media is relatively dominant in human use today, and until the way we interact and communicate using social media can understand identity in context is one area that attracts a lot of interest in using it. It is considered like a boon, as a way to connect many people and streamline communication. One of Baudrillard's thoughts is simulation in social media which becomes simulacra in digital advertising. Humans today live in a world full of simulation, almost nothing is real outside of simulation, nothing is genuine and can be imitated. Industrial culture disguises the distance between facts and information, between information and entertainment, between entertainment and political interests. The purpose of this research is to evaluate symbols or signs in political advertisements for the 2024 presidential election on social media. The method will be carried out with netnography through big data analysis by finding simulacra signs in digital advertisements for the 2024 presidential election. The existence of digital advertising in elections offers a great opportunity to increase voter participation and engagement. However, keep in mind that the use of digital advertising also brings challenges and responsibilities that must be handled wisely by all relevant parties.